IDENTIFIKASI KANDUNGAN LITIUM PADA BATUAN FILIT KOMPLEKS LUK ULO, JAWA TENGAH: LITHIUM IDENTIFICATION ON PHYLLITE FROM THE LUK ULO COMPLEX, CENTRAL JAVA - Isyqi; Setiawan, Nugroho Imam; Anggara, Ferian (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2024)
Production of lithium-ion batteries in Indonesia will be more feasible if Indonesia has its own lithium resources. Metapelitic rocks have the potential to serve as an alternate raw material for lithium. Phyllite, a type of metapelitic rock, was found in the Luk Ulo Complex, Central Java. The objective of this study is to determine the mineral composition and lithium concentration of the phyllite rocks from the Luk Ulo Complex. This will serve as a representative model for understanding the occurrence of lithium in similar rock types. The techniques employed to accomplish this objective include field surveys, petrographic, XRD, and ICP-AES/MS analysis. Phyllite in the Luk Ulo Complex is found in several locations and exhibits well-developed schistosity, characterized by a predominant mineral composition of quartz, graphite, chlorite, and white mica. The concentration of lithium in the phyllite from the Luk Ulo Complex exceeds the average concentration of lithium in the earth's crust, which typically ranges from 18.2 to 84.7 ppm. The presence of lithium in the phyllite rock is believed to be associated with the white mica minerals in the rock because the principal component analysis reveals a significant correlation between the lithium level in phyllite and the major elements K2O, CaO, Na2O, MgO, and Al2O3, which are responsible for the formation of the white mica. The phyllite rocks in the Luk Ulo Complex have a lithium enrichment that is five times more than the concentration of lithium in the earth's crust. It is believed that this enrichment is generated from the protoliths of the phyllite rocks, which are pelitic sedimentary rocks of continental origin. The presence of lithium in the phyllite rocks of the Luk Ulo Complex makes them suitable as lithium sources. However, due to their location within the Karangsambung Geological Reserve Area, these rocks are not to be exploited.